(untitled) (Revista de Ciências Agroveterinárias, 2011)
Canine Distemper is a contagious, severe and multisystemic disease caused by a virus from Morbillivírus genus. The virus is distributed worldwide and it presents a high lethality rate, affecting mainly dogs. The diagnosis is based on clinical signs associated with hematological findings. The observation of Lentz bodies in erythrocytes and leukocytes is the definitive diagnosis for the disease. The aim of this work was to test the hypothesis that the hematological profile in dogs positive for canine distemper differs according to blood cell type presenting Lentz bodies. For this purpose, 25 dogs positive for the disease were evaluated at the Veterinary Hospital “Luís Quintiliano de Oliveira” UNESP, Araçatuba city. The diagnosis was based on the observation of Lentz bodies in blood smears. From the total, 64% of dogs presented anemia, 16% leucopenia and 12% leukocytosis. Lymphopenia occurred in 76% of dogs. Viral inclusions were observed solely in neutrophils (32%), lymphocytes (28%) and erythrocytes (12%). Concomitant observation occurred in lymphocytes and erythrocytes (4%), in lymphocytes and neutrophils (12%), in neutrophils and monocytes (4%) and in neutrophils and erythrocytes (4%). In an isolated case Lentz bodies were observed simultaneously in neuthrophils, monocytes and lymphocytes. In conclusion, hematological profile is not associated with the presence of viral inclusion in a particular cell type.